Synthesis Of Molecularly Imprinted Polymer For Selective Solid-Phase Extraction Of Salbutamol From Urine Samples - Lee, Wei Inn (2011)
High selective molecularly imprinted polymers were synthesized to extracted salbutamol from human urine samples using structurally analogue template molecules. Molecularly imprinted polymers (MIPs) were prepared by using bamethane (BIP) and methylated salbutamol (CIP), two structural analogue of the targeted analyte, salbutamol as template. Free radical polymerization was conducted in a non-covalent approach using methacrylic acid (MAA) as functional monomer and ethylene glycol methacrylate (EGDMA) as cross-linking agent. The polymerization process was initiated by 2,2‟-azobisdimethyl valeronitrile and conducted at 50 ºC for 24 hours.